PENGARUH KOMUNIKASI DAN LINGKUNGAN KERJA FISIK TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. MUTIARA MUKTI FARMA - Marpaung, Fenny Krisna; Simamora, Kristopel; Hutauruk, Grace Sheila; Sitompul, Kiris Derita (JURNAL GLOBAL MANAJEMEN; Vol 8 No 1 (2019): JUNI, 2019)
Communication and physical work environment has an impact that must be considered by the company in order to support the work convenience of employees and lead to employees’ job satisfaction and maintain employees’ loyalty. With the existence of good communication and a supportive physical work environment, it is expected to maintain employees’ job satisfaction and support employees’ work productivity. Good communication between superiors and superiors, superiors with subordinates and subordinates with subordinates will guarantee both the information provided and received. A supportive physical work environment will increase the comfort and performance of employees. The purpose of this study was to find out how the implementation of communication and physical work environment conditions for employees’ job satisfaction at PT.Mutiara Mukti Farma. The method used in this research was quantitative descriptive. The amount of sample taken in this study amounted to 101 persons. This research was also conducted to see the effect of communication on employees’ job satisfaction and the effect of the physical work environment on employees’ job satisfaction